PENGARUH PERILAKU KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PEMBERDAYAAN PSIKOLOGIS DAN SUBTITUT KEPEMIMPINAN SEBAGAI VARIABEL PEMODERASI - YESSY ARTANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
The purposes of this research are to examine whether transformational leadership behavior significantly could explaine variance in OCB beyond be explained by transactional leadership behavior and to investigate the effects of transactional and transformational leadership behavior on OCB that moderated by psychological empowerment and substitutes for leadership. Samples of the research consists of middle-level managers in several manufactures in east java. The data were collected use 32 item leadership, 12 item psychological empowerment, 41 item substitutes for leadership, and 14 item OCB. The overall instruments those used in this study were perceptive instruments. Using purposive sampling method, 20 middle-level managers and their 90 staffs in manufactures in east java were collected. Of the 99 questionaires were distributed to staff and also 99 (different) questionaires for their manager in order to examine OCB of the staff, 90 staff’s questionaires were returned (response rate of 91%), and 90 questionaires from managers (response rate of 91%). Hierarchical regression analsis showed that when transactional leadership behavior was entered first, transactional leadership behavior could not explaine significantly variance in OCB. When transformational leadership behavior was entered second, transformational leadership behavior significantly could explaine variance in OCB, beyond be explained by transactional leadership behavior. This analysis also showed that psychological empowerment and substitutes for leadership significantly could moderate the effects of transactional and transformational leadership behavior on OCB.